2004
DOI: 10.1128/mcb.24.17.7524-7537.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and Proteolysis of Cancer-Derived Smad4 Mutants by SCFSkp2

Abstract: Smad4/DPC4, a common signal transducer in transforming growth factor beta (TGF-␤) signaling, is frequently inactivated in human cancer. Although the ubiquitin-proteasome pathway has been established as one mechanism of inactivating Smad4 in cancer, the specific ubiquitin E3 ligase for ubiquitination-mediated proteolysis of Smad4 cancer mutants remains unclear. In this report, we identified the SCF Skp2 complex as candidate Smad4-interacting proteins in an antibody array-based screen and further elucidated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 54 publications
(84 reference statements)
0
65
1
Order By: Relevance
“…Such mutations are R133C in Smad2 and L43S, G65V, R100T and P130S in Smad4. Among these mutant Smads, G65V and R100T Smad4 were shown to be targeted effectively by the SCF Ub ligase, which includes the F-box subunits Skp2 or bTrCP-1 for proteasomal degradation, whereas wild-type Smad4 was not targeted by this enzyme [59,62]. The ligases affecting other Smad4 or Smad2 mutants remain to be elucidated.…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mutations are R133C in Smad2 and L43S, G65V, R100T and P130S in Smad4. Among these mutant Smads, G65V and R100T Smad4 were shown to be targeted effectively by the SCF Ub ligase, which includes the F-box subunits Skp2 or bTrCP-1 for proteasomal degradation, whereas wild-type Smad4 was not targeted by this enzyme [59,62]. The ligases affecting other Smad4 or Smad2 mutants remain to be elucidated.…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
“…Smad4 mutations that lead to instability have been reported in many different human cancers (see the discussion later). The E3 ligase SCF Skp2 has been strongly implicated to mediate the degradation of these mutants [62].…”
Section: Regulation Of Co-smad Stabilitymentioning
confidence: 99%
“…Recent studies have demonstrated that TGFβ signaling pathway is tightly regulated by the UPS (ubiquitin-proteasome system), 14 where UPS targets various components of the TGFβ pathway including cytoplasmic second messengers, transmembrane bound receptors and accumulated nuclear proteins. [15][16][17] Our endeavor to search for TGFβ-induced fast turnover proteins led us to identify Skp2 as a rapidly degraded protein in response to TGFβ signaling. As shown in Figure 1A-C, Skp2 is rapidly degraded in response to TGFβ stimulation, which in turn results in accumulation of p27.…”
Section: Targeted Degradation Of Skp2 By Cdh1/apc Is Involved Inmentioning
confidence: 99%
“…Smad4 point mutations identified in pancreatic (L43S and R100T) and colorectal (G65V and P130S) cancers have a higher affinity for the βTrCP F-box protein, and consequently also show enhanced SCF βTrCP -mediated polyubiquitination and degradation as compared to wild-type Smad4 [82,88,89]. Significantly, Liang et al demonstrated that R100T, G65V, and L43S mutations result in massive phosphorylation of Smad4 by JNK/p38 MAPK, causing an increased affinity of mutant Smad4 not only for βTrCP, but also for Skp2 [90]. This confirms and extends on the important role of SCF-complexed F-box proteins in mutant Smad4 hyper-degradation.…”
Section: Interplay Of Smad4 Post-translational Modifications In Cancementioning
confidence: 99%